The evolution of compact massive quiescent and star-forming galaxies derived from the Re–Rh and Mstar–Mh relations. Issue 3 (22nd May 2021) - Zanisi, L; Shankar, F; Fu, H; Rodriguez-Puebla, A; Avila-Reese, V; Faisst, A; Daddi, E; Boco, L; Lapi, A; Giavalisco, M; Saracco, P; Buitrago, F; et al.
ABSTRACT: The mean size (effective radius R e ) of massive galaxies (MGs; M star > 10 11.2 M⊙ ) is observed to increase steadily with cosmic time. It is still unclear whether this trend originates from the size growth of individual galaxies (via, e.g. mergers and/or AGN feedback) or from the inclusion of larger galaxies entering the selection at later epochs (progenitor bias). We here build a data-driven, flexible theoretical framework to probe the structural evolution of MGs. We assign galaxies to dark matter haloes via stellar mass–halo mass (SMHM) relations with varying high-mass slopes and scatters σSMHM in stellar mass at fixed halo mass, and assign sizes to galaxies using an empirically motivated, constant and linear relationship between R e and the host dark matter halo radius R h . We find that (1) the fast mean size growth of MGs is well reproduced independently of the shape of the input SMHM relation; (2) the numbers of compact MGs grow steadily until z ≳ 2 and fall off at lower redshifts, suggesting a lesser role of progenitor bias at later epochs; (3) a time-independent scatter σSMHM is consistent with a scenario in which compact star-forming MGs transition into quiescent MGs in a few 10 8 yr with a negligible structural evolution during the compact phase, while a scatter increasing at high redshift implies significant size growth during the star-forming phase. A robust measurement of the size function of MGs at high redshift can set strong constraints on the scatter of the SMHM relation and, by extension, on models of galaxy evolution.